To Buy or Not to Buy Foreign Currency: The Interplay between Fear of Missing Out, Unplanned Buying Behavior and Post-Purchase Regret - Ögel, Serdar (Journal of Applied And Theoretical Social Sciences, 2022)
Since last six months, there has been an increase in foreign currency buying behaviors of individuals to protect the value of their assets due to dramatic increase in the value of foreign currencies against Turkish liras. However, besides the increase in the value of foreign currency against Turkish liras, the interactions among individuals stimulate them to purchase foreign currencies. In this context, the objective of the research is to explore the interplay between fear of missing out, unplanned buying behavior and post-purchase regret with respect to foreign currency buying behavior. Herein, fear of missing out is set as an independent variable; whereas unplanned buying behavior is determined as a variable that mediates the linkage between fear of missing out and post-purchase regret. The data are gained from 392 participants by employing convenience sampling. In an attempt to explore the proposed links between the variables, structural equation modelling is utilized. The findings report that fear of missing out significantly and positively influences unplanned foreign currency buying behavior of individuals and their post-purchase regret; while unplanned foreign currency buying behavior significantly and positively influences their post-purchase regret towards buying foreign currency. Besides, the findings indicate that unplanned foreign currency buying behavior partially mediates the link between fear of missing out and post-purchase regret. Overall, by shedding a light on understanding foreign currency buying behavior of individuals in last six months, the results of the study also contribute to individuals to realize their future foreign exchange buying behavior in a more planned way.